2017
DOI: 10.3928/1081597x-20170721-02
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser–Assisted Intraocular Lens Fragmentation: Low Energy Transection

Abstract: This case illustrates a novel and effective clinical application of the femtosecond laser. [J Refract Surg. 2017;33(9):646-648.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…90 In addition, the FL has been shown to be a useful and safe adjunct in a series of 47 eyes with subluxed cataracts selected for FLACS where manual CCC can be especially problematic due to lack of lens support to allow countertraction, with over 90% of the capsular bags successfully retained. 91 More recently, indicating its surgical potential, the FL has been used to transect IOLs which require exchange 92 and can be used without adverse effect in cataract surgery with coexisting phakic IOLs and low endothelial counts before phakic IOL removal. 93 The FL can also be used to perform a primary laser posterior capsulotomy just prior to or just after IOL insertion 94,95 and has been used to this effect in paediatric congenital cataract cases.…”
Section: Use Of Flacs In Complicated Cataract Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…90 In addition, the FL has been shown to be a useful and safe adjunct in a series of 47 eyes with subluxed cataracts selected for FLACS where manual CCC can be especially problematic due to lack of lens support to allow countertraction, with over 90% of the capsular bags successfully retained. 91 More recently, indicating its surgical potential, the FL has been used to transect IOLs which require exchange 92 and can be used without adverse effect in cataract surgery with coexisting phakic IOLs and low endothelial counts before phakic IOL removal. 93 The FL can also be used to perform a primary laser posterior capsulotomy just prior to or just after IOL insertion 94,95 and has been used to this effect in paediatric congenital cataract cases.…”
Section: Use Of Flacs In Complicated Cataract Surgerymentioning
confidence: 99%
“…More recently, indicating its surgical potential, the FL has been used to transect IOLs which require exchange 92 and can be used without adverse effect in cataract surgery with coexisting phakic IOLs and low endothelial counts before phakic IOL removal. 93 The FL can also be used to perform a primary laser posterior capsulotomy just prior to or just after IOL insertion 94,95 and has been used to this effect in paediatric congenital cataract cases.…”
Section: Use Of Flacs In Complicated Cataract Surgerymentioning
confidence: 99%
“…An experimental study showed that IOL fragmentation was feasible with FSL [113]. Anisimova et al [114] introduced a case in which a one-piece acrylic hydrophobic IOL was successfully transected using FSL with low energy parameters for explantation via a small corneal incision. Bala et al [115] also reported two cases in which FSL was used to transect hydrophilic acrylic IOL.…”
Section: Experimental Studies Regarding Potential Application Of the mentioning
confidence: 99%